You just need to distribute 2 across the quantity, and it becomes very straightforward.
2x + 4 = 13 - x.
3x = 9
x = 3
2006-10-20 05:15:55
·
answer #1
·
answered by DavidK93 7
·
0⤊
0⤋
Simplifying
2(x + 2) = 13 + -1x
Reorder the terms:
2(2 + x) = 13 + -1x
(2 * 2 + x * 2) = 13 + -1x
(4 + 2x) = 13 + -1x
Solving
4 + 2x = 13 + -1x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add 'x' to each side of the equation.
4 + 2x + x = 13 + -1x + x
Combine like terms: 2x + x = 3x
4 + 3x = 13 + -1x + x
Combine like terms: -1x + x = 0
4 + 3x = 13 + 0
4 + 3x = 13
Add '-4' to each side of the equation.
4 + -4 + 3x = 13 + -4
Combine like terms: 4 + -4 = 0
0 + 3x = 13 + -4
3x = 13 + -4
Combine like terms: 13 + -4 = 9
3x = 9
Divide each side by '3'.
x = 3
Simplifying
x = 3
2006-10-20 13:26:27
·
answer #2
·
answered by skm 2
·
0⤊
0⤋
2(x + 2) = 13 - x
expand the left side of the equation
2x + 4 = 13 - x
Collect like terms together
2x + x = 13 - 4
(if -x goes to the left side of the equation, it becomes +x, like wise +4 becomes -4)
3x = 9
(3x)/3 = 9/3
x = 3
2006-10-20 17:08:07
·
answer #3
·
answered by Loral 2
·
0⤊
0⤋
These problems are more simple than your teachers allow u to think they are.
First, u see that 2 on the outside of 2(x+2), go a head and multiply each term by the two, it's called the DISTRUBUTIVE PROPERTY.
So 2(x+2) become 2x+4, (drop the parethesis)
Okay now ur problem looks like this
2x+4=13-x
get the X all on one side, so just pick a which one u wanna move(either the 2x or the x(near the 13)
I'm gonna pick the x by it self
The x by it self is being subtracted right,so ur gonna add it to both side.
Write +x underneath 13-x(line up the both x's) cross them out cuz they cancel out.
now write it under 2x+4=13,adding the one x to the 2x.
now ur new prblem is 3x+2=13
GREAT!! IT'S SIMPLE NOW!
subtract 2 from both sides,(just like u did that x)
now u got 3x=11
divide both sides by 3
u get x=3.66
2006-10-20 12:29:31
·
answer #4
·
answered by Gifted and Gracious 3
·
0⤊
0⤋
2(x + 2) = 13 - x
2x + 4 = 13 - x
2x + 4 + x = 13 - x + x
3x + 4 = 13
3x + 4 - 4 = 13 - 4
3x = 9
3x/3 = 9/3
x = 3
The answer is x = 3
Insert the x value into the equation
- - - - - - - - - - - - - - - - - -
Check
2(x + 2) = 13 - x
2(3 + 2 ) = 13 - 3
2(5) = 10
10 = 10
- - - - - - - - -s
2006-10-20 12:28:43
·
answer #5
·
answered by SAMUEL D 7
·
0⤊
0⤋
2(x + 2) = 13 - x
2x + 4 = 13 - x (Add x and subtract 4 from both sides)
3x = 9 (Divide both sides by 3)
x = 3
Check:
2(3 + 2) = 13 - 3
2(5) = 10
10 = 10
QED
2006-10-20 14:14:05
·
answer #6
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
2(x + 2) = 13 - x
2x + 4 = 13 - x
2x + x = 13 - 4
3x = 9
x = 9 / 3
x = 3
2006-10-20 12:21:43
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
2(x+2) = 13 - x
2x +4 = 13 -x
2x + 4 -4 =13 - x - 4
2x = 9 - x
2x +x = 9 -x +x
3x =9
3x/3 =9/3
x=3
2006-10-20 20:59:27
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
2(x+2)=13-x (first multiply x+2 by two)
2x+4=13-x (move the x to the other side)
3x+4=13 (move the number to one side)
3x=13-4 (simplify)
3x=9 (divide 9 by three)
x=3 YOU'VE GOT IT
2006-10-20 12:20:40
·
answer #9
·
answered by Ifeelgood 2
·
0⤊
0⤋
2x + 4 = 13 - x
add x to both sides
3x + 4 = 13
subtract 4 from both sides
3x = 9
divide both sides by 3
x = 3
2006-10-20 12:17:44
·
answer #10
·
answered by JJ M 2
·
0⤊
0⤋